Analisis Motivasi Mahasiswa PAI 2020 UIN Malang dalam Mengikuti Program Fast Track - Oktiviana, Nindia; Rossidy, Imron (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This study aims to analyze the motivations of students from the Islamic Education (PAI) class of 2020 at UIN Malang in participating in the Fast Track Program, as an effort to expedite higher education and increase the number of graduates in the Master's program. The research employs a qualitative approach with field research methods. Data were collected through observations, interviews, and documentation over a period of two weeks in June 2024. The findings indicate strong support among students for the program, viewing it as an opportunity to accelerate their professional careers. However, students face challenges such as heavy credit loads and overlapping class schedules. With appropriate support, including effective time management and career guidance, the program can be enhanced to optimize academic and career achievements for students.